2013
DOI: 10.1038/srep01008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-folate combination therapies and their effect on the development of drug resistance in Plasmodium vivax

Abstract: Can we predict the rise and spread of resistance to multi-drug therapy in a more predictable manner? We raise this question after analyzing over 500 Plasmodium vivax isolates collected from different, geographically isolated regions of China for sequence variation in and around the dhfr and dhps genes. We find: that resistance lineages have arisen at least once in each region; that there appears to have been little movement of parasite populations between these areas; and that highly resistant parasites contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
3
22
2
Order By: Relevance
“…This observation supports the presumption that the pfdhps resistance takes place only after a substantial fraction of the population has been selected for pyrimethamine resistance (22,33,34), and it likely reaffirms the previous clinical finding that mutations in the pfdhfr gene plays a major role in the failure of SP treatment against falciparum malaria (35,36). Though the SP drug selection was assumed to act independently and differently on dhfr and dhps loci (37,38), the asymmetry in the selection pattern suggests a potential genetic linkage between the two loci across chromosomal boundaries during the coselection of the drug combination (22,31). In this study, LD analysis of the pfdhfr and pfdhps alleles discovered strong linkages of some SNPs between the major high-level resistance alleles in the population.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This observation supports the presumption that the pfdhps resistance takes place only after a substantial fraction of the population has been selected for pyrimethamine resistance (22,33,34), and it likely reaffirms the previous clinical finding that mutations in the pfdhfr gene plays a major role in the failure of SP treatment against falciparum malaria (35,36). Though the SP drug selection was assumed to act independently and differently on dhfr and dhps loci (37,38), the asymmetry in the selection pattern suggests a potential genetic linkage between the two loci across chromosomal boundaries during the coselection of the drug combination (22,31). In this study, LD analysis of the pfdhfr and pfdhps alleles discovered strong linkages of some SNPs between the major high-level resistance alleles in the population.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, LD analysis of the pfdhfr and pfdhps alleles discovered strong linkages of some SNPs between the major high-level resistance alleles in the population. In another, parallel study on P. vivax isolates from Yunnan, we have shown that the high-resistance mutations in positions 57, 61, and 117 of pvdhfr (chromosome 5) and position 383 of pvdhps (chromosome 14) are genetically linked (31). Little is known about when and how these genetic linkages of certain SNPs in the dhfr and dhps genes took place across chromosomal boundaries, but it has been proved that such genetic relationships tend to induce the emergence and development of multiple drug resistance mutations and stabilize them within a parasite population after use of the drugs has been ceased for as long as 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrimethamine was added to table salt in some countries, including Brazil in the 1950s. 4,5 Although P. vivax alleles conferring resistance to pyrimethamine are well known 6-9 and are found in the Amazon basin, alleles conferring resistance to chloroquine, artemisinin, and primaquine (the only therapy that prevents vivax malaria relapse) in P. vivax remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…A similar warning has now been raised for combination treatment of malaria due to the discovery of high association among resistance alleles in multiple regions of China (Ding et al. ). Furthermore, a clear understanding of epistasis among resistance mutations is key to predicting the spread of multidrug‐resistant bacteria, as has been nicely demonstrated by Borrell et al.…”
mentioning
confidence: 97%